Dreaming of a better ILS. - Bahr E (Computers in Libraries, 2007)
Lots of people dream about what they'd want in a 'new and improved' ILS. CIL asked this author to put the question to a number of library tech experts, then study their responses. Here she reports on the wishes they all have in common and the dreams of the individuals.